Az Alföld-tünetcsoport újraéledése 1990–1994 - Csatári, Bálint (Tér és Társadalom, 1993)
The study analyses the Syndrome-like regional problems of one of the most characteristic Hungarian Macroregions. The relative, and in different historical eras unique historical-economic underdevelopment of this region became the scene of new, serious environmental, economic and social crises following the Hungarian systemic change. The analysis enumerates these, proves their continuity, and points to the new spatial changes that may show the most important regional developmental directions in the future. When it comes to the environmental sphere, the growing aridity and the disintegration of the balance of water-supply are the most serious problems. The economic crisis resulted in a high rate of unemployment due to both the loss of the markets and change of owners in agriculture, and the elimination of the unorganically settied subsidiaryindustry. The modernisation of the settlement network is hindered by the low levei of quality of the tertiary industries (with the exception of a few big towns) and the general underdevelopment of infrastructure. In addition there is the lanting lagging behind of some Eastern border regions, and also the complicated situation of the international connections and the passability of the borders. An almost continuous index of social conflict in this area has been the high suicide rate for one and a half centuries.